Factor Analysis of Sustainable Procurement Implementation in the Public Sector Construction Industry - Aisha, Della; Wiguna, I Putu Artama (Journal of Civil Engineering, 2025)
Public procurement holds significant potential to advance a country's sustainability agenda due to its substantial procurement volume. However, the gap between the principles of sustainable construction and their implementation in Indonesia remains suboptimal, with limited studies addressing sustainable procurement in the construction sector. Therefore, this research aims to identify the factors of the implementation of sustainable procurement in the public sector of the construction industry. Data were collected through a questionnaire survey involving 50 respondents from the procurement department of the Ministry of Public Works and Housing (PUPR). The research used a 5-point Likert scale for measurement, and data were analyzed using exploratory factor analysis. This research found five main factors in sustainable procurement practices, namely: environmental purchasing, implementation of management systems, implementation of economic benefits, implementation of government regulations, and social procurement